Adverse fetal outcome: is first trimester ultrasound and Doppler better predictor than biomarkers?. (18th June 2017) - Kumar, Manisha; Singh, Shalini; Sharma, Karuna; Singh, Ritu; Ravi, V.; Bhattacharya, J.
Abstract: Aims and objectives : To evaluate the predictive value of first trimester biomarkers and ultrasound in determining adverse fetal outcomes in a low risk Asian population. Material and method : All low risk, singleton pregnancies between 11 and 14 weeks gestation underwent ultrasound with uterine artery Doppler along with PAPP-A and free β-hCG estimation, and were followed till delivery to observe the outcome. The adverse fetal outcomes detected were structural anomaly, aneuploidy, intrauterine growth restriction, preterm birth and stillbirth (SB). Results : Out of 3500 women screened, 417 cases had adverse fetal outcome in the absence of maternal complication, 2151 had normal outcome. Major structural anomaly was detected in first trimester in 17/28 (60.7%) cases. The most important markers for adverse fetal outcome were increased uterine artery pulsatility index (UPI) ( p  = 0.028, OR 1.5, 95% CI: 1.05–2.38, AUC 0.56) for IUGR, nuchal translucency ( p  = 0.001, OR 1.7, 95% CI: 1.11–2.77, AUC 0.60) for major anomaly and low PAPP-A ( p  = 0.017, OR −0.075, 95% CI: 0.87–0.98, AUC 0.621) for SB. Conclusion : UPI, NT and PAPP-A in the first trimester are significant markers of adverse fetal outcome, although the sensitivity and specificity are not high they have a high negative predictive value.